Implementasi Metode Simple Additive Weighting (SAW) Untuk Pemilihan Supplier Pakan Ternak Pada Toko Pakan Selo - Ega Arya Chalandra Daniswara; Pradityo Utomo Pradityo Utomo; Sukadi Sukadi (PT Mekar Research and Publishing, 2025)
In the business world, particularly in the livestock feed trade, selecting the right supplier is a crucial factor in maintaining business continuity. However, the supplier selection process is often carried out manually and subjectively, which increases the risk of decision-making errors. This is evident in the case of selecting the best livestock feed supplier at Toko Pakan Selo. This study utilizes a Decision Support System (DSS) employing the Simple Additive Weighting (SAW) method, as Simple Additive Weighting (SAW) is capable of evaluating various alternatives based on multiple criteria, such as feed price, feed quality, delivery accuracy, distance to location, and product availability. The system developed is expected to enhance the effectiveness, efficiency, and objectivity of the supplier selection process. Furthermore, the system aims to replace the traditional manual method with a web-based digital solution. The results of system testing indicate that the system is capable of assisting Toko Pakan Selo in identifying the best supplier and supporting the stability of livestock feed supply. Based on black-box testing, the system functions as intended.